2023
DOI: 10.3390/ijms24054498
|View full text |Cite
|
Sign up to set email alerts
|

Dual PTP1B/TC-PTP Inhibitors: Biological Evaluation of 3-(Hydroxymethyl)cinnoline-4(1H)-Ones

Abstract: Dual inhibitors of protein phosphotyrosine phosphatase 1B (PTP1B)/T-cell protein phosphotyrosine phosphatase (TC-PTP) based on the 3-(hydroxymethyl)-4-oxo-1,4-dihydrocinnoline scaffold have been identified. Their dual affinity to both enzymes has been thoroughly corroborated by in silico modeling experiments. The compounds have been profiled in vivo for their effects on body weight and food intake in obese rats. Likewise, the effects of the compounds on glucose tolerance, insulin resistance, as well as insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, gaining insights into the functional roles of PTP1B and TC-PTP in cellular signaling, they are both capable of attenuating the insulin and leptin signaling pathways by dephosphorylating their receptor and downstreaming signal molecules. Consequently, the concurrent inhibition of PTP1B and TC-PTP holds the potential to yield synergistic benefits across a range of therapeutic applications, encompassing type 2 diabetes, obesity, and anticancer immunotherapies. ,,,, As illustrated in Table , S2 , S6 , A2–17 , and A2–21 all exhibited excellent PTP1B inhibitory activity as well as good TC-PTP inhibitory activity. These results established the potential for peptide-based inhibitors of PTP1B and TC-PTP to enhance their in vivo anti-T2DM efficacy and could provide a proof-of-concept for PTP1B/TC-PTP dual targeting as a therapeutic approach for T2DM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, gaining insights into the functional roles of PTP1B and TC-PTP in cellular signaling, they are both capable of attenuating the insulin and leptin signaling pathways by dephosphorylating their receptor and downstreaming signal molecules. Consequently, the concurrent inhibition of PTP1B and TC-PTP holds the potential to yield synergistic benefits across a range of therapeutic applications, encompassing type 2 diabetes, obesity, and anticancer immunotherapies. ,,,, As illustrated in Table , S2 , S6 , A2–17 , and A2–21 all exhibited excellent PTP1B inhibitory activity as well as good TC-PTP inhibitory activity. These results established the potential for peptide-based inhibitors of PTP1B and TC-PTP to enhance their in vivo anti-T2DM efficacy and could provide a proof-of-concept for PTP1B/TC-PTP dual targeting as a therapeutic approach for T2DM.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a recent study found that combined intranasal targeting of hypothalamic PTP1B and TC-PTP reinstated leptin and insulin sensitivity and promoted weight loss in obesity . Another report showed that PTP1B/TC-PTP dual inhibitors could potentially emerge as a promising avenue for the development of drugs for the treatment of metabolic disorders, including type 2 diabetes mellitus (T2DM), obesity, and hyperphagia. Moreover, the proteolysis-targeting chimera approach , has been adopted to transform the PTP1B/TC-PTP dual inhibitors into degraders for both PTP1B and TC-PTP .…”
mentioning
confidence: 99%
“…2 As shown in Figure 1, some of the cinnoline-containing compounds are reported as inhibitors of phosphoinositide 3kinase (PI3K), 3 Bruton's tyrosine kinase (BTK), 4 human neutrophil elastase (HNE), 5 protozoan parasite growth, 6 c-MET kinase, 7 ataxia telangiectasia mutated (ATM), 8 colonystimulating factor 1 receptor (CSF-1R), 9 phosphodiesterase 10A (PDE-10A), 10 leucine-rich repeat kinase 2 (LRRK-2), 11 and scytalone dehydratase (SD), 12 and also described as the anti-inflammatory agent, 13 dual non-acidic anti-inflammatory− antibacterial agent, 14 binding selective liver X receptor β (LXRβ) agonist, 15 (PTP1B)/T-cell protein phosphotyrosine phosphatase (TC-PTP). 17 The importance of cinnoline-based molecules in medicinal chemistry has caused the synthesis of cinnoline nucleus and cinnoline-containing heterocyclic scaffolds in the spotlight. In this regard, the design and/or use of simple and efficient synthetic strategies for the preparation of such precious compounds is worthwhile.…”
Section: Introductionmentioning
confidence: 99%
“…Cinnoline (also known as benzo­[ c ]­pyridazine, 1,2-benzodiazine, and 1,2-diazanaphthalene) is one of the most valuable fused heterocyclic systems, which exhibits a broad spectrum of pharmacological activities, and interestingly some of them are under evaluation in clinical trials . As shown in Figure , some of the cinnoline-containing compounds are reported as inhibitors of phosphoinositide 3-kinase (PI3K), Bruton’s tyrosine kinase (BTK), human neutrophil elastase (HNE), protozoan parasite growth, c-MET kinase, ataxia telangiectasia mutated (ATM), colony-stimulating factor 1 receptor (CSF-1R), phosphodiesterase 10A (PDE-10A), leucine-rich repeat kinase 2 (LRRK-2), and scytalone dehydratase (SD), and also described as the anti-inflammatory agent, dual non-acidic anti-inflammatory–antibacterial agent, binding selective liver X receptor β (LXR-β) agonist, mGlu 7 positive allosteric modulator (PAM), and dual inhibitor of protein phosphotyrosine phosphatase 1B (PTP1B)/T-cell protein phosphotyrosine phosphatase (TC-PTP) …”
Section: Introductionmentioning
confidence: 99%